PENGEMBANGAN SKENARIO PEMBELAJARAN AKTIF BERBASIS MIKiR UNTUK SISWA KELAS V PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Reflina Reflina; Riris Nurkholidah Rambe (Universitas Bhinneka PGRI, 2024)
Learning scenario is the important thing in teaching process. Designing of good learning scenario is one of effort to increase learning quality. The aims of this study is to see the validity and practicality of the developed MIKiR-based active learning scenario. This study was carried out at the Integrated Islamic Elementary School (SDIT) Nurul Ilmi with the number of study subjects are 40 students from two fifth grades of Mathematics. The method used to develop the MIKiR-based active learning scenario is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The study instruments used in this study were: validation sheets to measure product feasibility, and teacher response questionnaires to see the practicality of the product. The results obtained are as follows, for the level of validity of the MIKiR-based active learning scenario, the average score is 3.67 with a very valid category consisting of three aspects, namely content, material, form, presentation, language, and legibility. Furthermore, the level of practicality obtained a very practical category with an average value of 84.76%. This can be seen from four aspects, namely the attractiveness of the device to student interest, ease of use and content, increased student activity, and time efficiency.